2011
DOI: 10.1021/jp201201x
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field-Induced Perfect Anti-Nematic Order in Isotropic Aqueous Suspensions of a Natural Beidellite Clay

Abstract: We study the electric-field-induced birefringence and orientational order in the isotropic phase of aqueous suspensions of exfoliated natural beidellite clay particles, thin (L = 0.65 nm) flat charged sheets with high aspect ratio, D/L ≈ 300. Our electric birefringence experiment is optimized for aqueous suspensions of colloidal particles, with a high frequency a.c. electric field, ν ≈ 1 MHz, applied by two external electrodes to a thin flat sample, sealed in an optical capillary. In isotropic and biphasic sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(148 citation statements)
references
References 88 publications
6
142
0
Order By: Relevance
“…At larger fields, deviation from this law due to saturation of the birefringence is observed, in agreement with the data reported elsewhere 22 where it was found that linearity with E 2 0 is lost above 20 V/mm for similar clays. Hereafter all experiments are performed with an electric field of 10 V/mm and hence, the Kerr constant can be properly used.…”
Section: General Featuressupporting
confidence: 92%
See 3 more Smart Citations
“…At larger fields, deviation from this law due to saturation of the birefringence is observed, in agreement with the data reported elsewhere 22 where it was found that linearity with E 2 0 is lost above 20 V/mm for similar clays. Hereafter all experiments are performed with an electric field of 10 V/mm and hence, the Kerr constant can be properly used.…”
Section: General Featuressupporting
confidence: 92%
“…For example, at 1 MHz, the value of the electrical polarizability is α e a = −5.49 × 10 −28 Fm 2 along the symmetry axis and α e b = 2.41 × 10 −27 Fm 2 along the particle surface. In this case, the polarizability anisotropy per unit volume, ∆α e /V p = 3.7 × 10 −9 F/m, is comparable to values obtained elsewhere 14,22 for similar materials.…”
Section: General Featuressupporting
confidence: 86%
See 2 more Smart Citations
“…This effect was recently described in clay suspensions [47][48][49][50][51][52], in which the liquidcrystalline character is evidenced by polarised light microscopy and small-angle X-ray scattering. These experiments on clay-based gel samples reveal strong positional and orientation orders of the particles, proving unambiguously the nematic character of the clay mineral-rich gel.…”
Section: Discussionmentioning
confidence: 72%